PAS‐C platelets contain less plasma protein, lower anti‐A and anti‐B titers, and decreased HLA antibody specificities compared to plasma platelets. Issue 4 (22nd February 2018) - Weisberg, Stuart P.; Shaz, Beth H.; Tumer, Gizem; Silliman, Chris C.; Kelher, Marguerite R.; Cohn, Claudia S.
Abstract : BACKGROUND: Platelets (PLTs) collected and stored in PLT additive solution Intersol (PAS‐C) are presumed to reduce recipient exposure to donor plasma components; however, the effects of PAS‐C on PLT supernatant composition are poorly defined. Therefore, we compared the total protein concentration, isohemagglutinin titers, and HLA antibodies in supernatants of PAS‐C PLTs to plasma PLTs. STUDY DESIGN AND METHODS: Apheresis PLTs from group O blood donors were collected into either 100% donor plasma (n = 50) or a mixture of 65% PAS‐C/35% donor plasma (n = 50). Within 12 hours of collection, samples of the PLT supernatant were frozen and stored. PLT supernatants were assayed for total protein concentration and anti‐A and anti‐B titers and screened for HLA antibodies. Samples positive for HLA antibodies were further tested using single‐antigen bead assays to determine antibody strength and specificity. RESULTS: Supernatants of PAS‐C PLTs had significantly lower total protein concentration and anti‐A and anti‐B titers compared to plasma PLTs. There was no significant difference in the number of HLA antibody screen–positive PAS‐C (3/50) compared to plasma PLT supernatants (2/50); however, the HLA antibody screen–positive supernatants of PAS‐C PLTs had fewer HLA specificities (2) compared to those of the plasma PLTs (18). CONCLUSION: Decreased plasma proteins likely underlie lower rates of allergic and febrile, nonhemolytic transfusion reactions from the infusion of PAS‐C PLTs. Decreased anti‐A and anti‐B titers may prevent hemolysis from minor ABO mismatch. Lower HLA antibody specificities may mitigate transfusion‐related acute lung injury.